PENGARUH RASIO PASAR DAN KEPUTUSAN INVESTASI TERHADAP HARGA SAHAM PADA PT BUKIT ASAM TBK PERIODE 2017 - mali, Yohanes fisker Koli; Sanjaya, Rudi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the effect of Market Ratio and Investment Decision on Stock Price at PT Bukit Asam Tbk for the period 2017–2024. The research method used is a quantitative approach with multiple linear regression analysis. Data were obtained from annual financial reports and the analysis was carried out using SPSS Statistics version 25. The results of the study show that partially, Market Ratio (PER) has a significant effect on Stock Price with a calculated t value of 5.495, so that t-count> t-table 5.495> 2.01505. significance 0.003 <0.05, while Investment Decision (ROA) does not have a significant effect partially with a calculated t value of 1.504, so that t-count <t-table 1.504 <2.01505. significance 0.193> 0.05. simultaneously, Market Ratio (PER) and Investment Decision (ROA), have a significant effect on Stock Price. This is indicated by the calculated F-value of 17.175 which is greater than the F-table of 5.79, with a significance value of 0.006 <0.05. The coefficient of determination value shows that 82.2% of the variation in Stock Prices can be explained by the Market Ratio (PER) and Investment Decision (ROA) variables. Meanwhile, the remaining 17.8% is influenced by other variables outside the model that are not discussed in this study. This finding indicates that the Market Ratio is a more dominant indicator in influencing stock prices than Investment Decisions during the study period.